The Marine Algae of the Pacific Coast of North America. - Setchell, William Albert; Gardner, Nathaniel Lyon (Stechert-Hafner, 1967)
Reprinted from University of California Publications in Botany, Vol. 8, pt. 1-3, November 29, 1919 - June 1925. Includes bibliographies. Contents: Pt. 1. Myxophyceae. Pt. 2. Chlorophyceae